Assessing Prospective Teachers' Readiness: An Integrative Study of Teaching Methods and the Achievement of 21st Century Competencies in the Primary Teacher Education Department - Rahman, Hardianto; Sayidiman; Irfan, Muhammad; Syamsuddin, Afdhal Fatawuri; Yusnadi (Jurnal Pendidikan Dasar dan Keguruan, 2026)
The transformation of education in the 21st century requires prospective teachers to have competencies that are adaptive to the changing times, such as critical thinking, creativity, collaboration, communication, and digital literacy. This study aims to 1) analyze the relationship between the teaching methods applied in the primary teacher education Department at Universitas Negeri Makassar (UNM) and the achievement of prospective teacher students' competencies in 21st-century skills; 2) identify the dominant learning paradigm and its impact on 21st-century skills; 3) map the level of student competency achievement in 21st-century skills and identify the factors that support and hinder the achievement of 21st-century skills. The research method used was a combination of quantitative and qualitative research (mixed method), with data collection using surveys and interviews, selected and implemented with consistency and accuracy. Quantitative data were analyzed using statistical techniques, while qualitative data were analyzed using thematic analysis. The research sample consisted of 250 students and 35 lecturers. The results of this study reveal that: the majority of the students teacher are at an intermediate level of competence in 21st-century skills; only a small proportion have reached an advanced level, and almost none have reached an expert level; there are variations in achievement between indicators; teaching methods and learning paradigms play a significant role in supporting or limiting these achievements; emotional support, self-reflection, and technology integration are aspects that need to be strengthened.